2015
DOI: 10.1002/pola.27566
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of thermosensitive functional polyaspartamide derivatives by click chemistry

Abstract: Biodegradable and thermosensitive polyaspartamide derivatives containing pendant azide groups P(Asp‐Az)X‐HPAs were synthesized from poly(l‐succinimide) via the ring‐opening reaction with 2‐azidoethylamine (Az) and 5‐hydroxypentylamine (HPA). Then hydrophobic phenethyl (PEA) and imidazole (IMZ) moieties were introduced successfully with very high reaction efficiency above 90% to the side chains of P(Asp‐Az)X‐HPA by click reaction to obtain thermoresponsive polyaspartamide derivatives containing pendant aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The structures of the obtained NB ‐g‐ PHPA polymers were studied by 1 H‐NMR analysis as shown in Figure . No signals located between 5 and 6 ppm in Figure (A) indicated that the rings of PSI were completely opened by 5‐amino‐1‐pentanol . The characteristic signal at 5.5 ppm in Figure (B) was assigned to the methylene protons (k) between carbonate ester and phenyl group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of the obtained NB ‐g‐ PHPA polymers were studied by 1 H‐NMR analysis as shown in Figure . No signals located between 5 and 6 ppm in Figure (A) indicated that the rings of PSI were completely opened by 5‐amino‐1‐pentanol . The characteristic signal at 5.5 ppm in Figure (B) was assigned to the methylene protons (k) between carbonate ester and phenyl group.…”
Section: Resultsmentioning
confidence: 99%
“…As an important smart material, stimuli‐responsive polymeric micelles have recently received considerable attention in drug carriers, due to their response to specific physicochemical signals (e.g., heat, pH, redox, light, and ultrasound), which allows polymeric micelles to achieve targeted delivery and controlled release of drugs . Especially, light‐sensitive polymeric micelles have shown promising prospect and huge potential for biomedicine applications, because light is a clean and efficient stimulation source that can be triggered on and off from outside of the system, and controlled easily at a specific time and location .…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol monomethyl ether (mPEG) was from Sigma-Aldrich (Louis, MO, USA) ( M n = 4431, M w / M n = 1.28). Phenethyl prop-2-ynyl carbonate (PPA-PEA), 2-azidoethylamine and PSI were synthesized as reported in a previous study [ 29 ]. All other reagents and solvents were of analytical grade and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Click chemistry usually possesses high reaction selectivity and efficiency, and has been widely applied in the biomedical field for preparing stimuli responsive polymers for anti-cancer drug delivery [ 2 , 28 ]. Based on the work related to PHPA, we designed an azide-functional polyaspartamide derivative P(Asp-Az)-HPA which was composed of about 40% 2-azidoethyl moiety and 60% 5-hydroxypentyl moiety in its side chains (molar percentage), and illustrated an easy way to synthesize temperature responsive polyaspartamide-based polymers by grafting hydrophobic moieties, such as phenyl alcohol, to the side chains of P(Asp-Az)-HPA via a click reaction with high grafting efficiency above 90% [ 29 ]. However, no real applications in drug delivery were mentioned for the obtained P(Asp-Az)-HPA-based temperature responsive polymers because of the low stabilities of their formed nanoparticles in salt conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli‐responsive polymeric micelles receive great attention in drug delivery systems . This is attributed to the specific nanostructures and properties in response to specific physicochemical signals (e.g., heat, pH, light, and ultrasound), which allow polymeric micelles to achieve their long‐circulation in blood and targeted delivery of drugs . Specially, pH‐responsive polymeric micelles have been widely studied for rapid, acidic pH‐triggered anticancer drug release inside tumor cells, because the extracellular pH (pH e ) of normal tissues and blood pH are at about 7.4, whereas the tumor pH e is about 6.5 and the pH of endosomes and lysosomes are even lower (pH 5.0–5.5) .…”
Section: Introductionmentioning
confidence: 99%